Implementasi Web Scraping pada Google Cendekia sebagai Sarana Profiling Penelitian Dosen - Muhammad Koprawi; Wahyu Sukestyastama Putra (Universitas Sarjanawiyata Tamansiswa, 2023)
Google Scholar is an online platform that provides access to scholarly literature such as articles, theses, books and conference proceedings from various scientific publishers. As educators or lecturers, they should have scientific research works that can be accessed by anyone at any time. To measure achievement and access to publication of scientific papers quickly and to profiling educators, lecturers or researchers, universities must have a centralized database that comes from a Google Scholar account and can be updated periodically or automatically based on a specified period. To solve this problem, the researcher implements a web scraping technique combined with a cron job as a command that will run a task on a scheduled basis. The method used is the RAD (Rapid Application Development) method which focuses on a fast system development process. This study succeeded in scraping data for 2983 documents, displaying document citation data globally and successfully carrying out an automatic scheduling synchronization process that is set with scheduling configurations every week, every month, every quarter, every semester and every year, and scripts on cron jobs are run every 5 minutes on the server to check if any scheduling is active.